The Determinants of Banking Stock Returns in Indonesia Using Intervalling Method - Jati, Damar Kartika; Fachrurrozie, Fachrurrozie (Accounting Analysis Journal, 2021)
This study aims to analyze the effect of LDR, ROA, CAR, EPS, and DER on stock returns by the method of intervalling. This study takes the banking population listed on the Indonesia Stock Exchange (BEI) in 2015-2017 as many as 45 banks. The sampling technique used purposive sampling and obtained 25 banks so that 150 units of analysis for data 6 months and 75 units of analysis for data 12 months. The data uses semester, annual financial reports, and stock closing prices for 2015-2017. The multiple regression analysis method was used in this study with the IBM SPSS 21.0 analysis tool. The results of data analysis show that CAR has a significant positive effect on stock returns at intervals of 6 and 12 months. ROA has a significant negative effect on stock returns at 12-month intervals. LDR, EPS, and DER do not affect stock returns. The conclusion of this study is that CAR can affect stock returns. Keywords: Stock Return, Loan to Deposit Ratio; Return on Assets; Capital Adequacy Ratio; Earning per Share; Debt to Equity Ratio